The Effect of Virtual Reality Game Training on Improving Walking Speed and Dynamic Balance Function After Stroke - Lampah, Christopher; Berhimpon, Siemona L. E.; Durry, Meilany Feronika; Anggana, Brain; Suyono, Jonathan Prayogi; Setiono, Alfred (Faculty of Medicine, Universitas Airlangga, 2024)
Background: Stroke is a serious health condition that can cause physical and cognitive impairment, affecting a person's ability to perform daily activities. Important factor that affect the quality of life of stroke patients is the ability to mobilize, especially walking. Virtual Reality is expected to increase walking speed and dynamic balance which are important to improve patient mobility and independence. Aim(s) : Analyse the effect of Virtual Reality (VR) game training using Xbox 360° and KinectTM devices on post-stroke walking speed and balance Material and methods: An experimental study involving 18 ischemic post-stroke patients at the Rehabilitation Installation of Prof. Dr. R. D. Kandou Hospital Manado (from June to July 2023). The intervention was a 30 minutes VR game exercises with three sessions per week (a total of 8 sessions for each subject). This subject was assessed using the 10-meter Walk Test (10 MWT) and the Berg Balance Scale (BBS). Result: There were significant improvements in both walking speed and dynamic balance. Wilcoxon Signed Ranks test results on Walking Speed (10 MWT) obtained a value of Z = -3,754 with a value of (p = 0.000 <0.05). Similar results were obtained in testing the dynamic balance function where the paired t test results were obtained at t = -14.750. The results indicate significant differences in the mean value of Subacute Post-Stroke BBS before and after training (p < 0.05). Conclusions: Virtual Reality (VR) game training using Xbox 360° and KinectTM devices significantly increased walking speed and balance in post-stroke patients.